STRATEGI KOMUNIKASI LINGKUNGAN KELOMPOK MASYARAKAT PEDULI ALAM SEKITAR (KEMPAS) DALAM MENGELOLA EKOWISATA MANGROVE DESA SEBAUK KECAMATAN BENGKALIS KABUPATEN BENGKALIS - Muhammad Trisna Hadikurnia; Yasir " (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2019)
Mangrove Ecotourism in Sebauk Village is one of the programs managed by the Community Nature Care Group or KEMPAS. Management of mangrove ecotourism is a form of public awareness to protect the environment from the damage that occurred in the coastal area of the Sebauk Village. Therefore, this study tries to study the KEMPAS environmental communication strategy, how to develop KEMPAS and how the KEMPAS communication model in the effort to manage mangrove ecotourism in Sebauk Village, Bengkalis Sub-District.             This study uses qualitative research methods using descriptive. The research subjects were 8 informants who were selected using a purposive technique. Data collection is done through in-depth interviews, observation and documentation. To do the data validity, the author uses the technique of extending participation, perseverance monitoring and triangulation. The results of this study indicate that the KEMPAS environmental communication strategy is carried out through several stages. First, the assessment stage includes situation analysis and problem identification. Second, planning discussions that include communication strategies, motivating and community mobilization, media selection. Third, the production stage includes message design, media production. Fourth, the implementation phase which includes dissemination through media, documentation and evaluation. Guidance has been carried out from several government agencies such as the Department of Maritime Affairs and Fisheries and the Office of Environment related to the mangrove ecotourism program, namely by providing socialization, guidance, training, monitoring, facilitators and also providing assistance in the form of mangrove seedlings. The communication model used by KEMPAS is the Kincaid partnership communication model. The convergence communication model is considered more effective and efficient in achieving mutual understanding in a deliberation.   Keywords: Environmental Communication. Ecotourism mangroves, KEMPAS